CARDIOVERSION WITH BI- AND MONOPHASE DEFIBRILLATORS IN PATIENTS WITH PAROXYSMAL ATRIAL FIBRILLATION - V. A. Lusov; I. A. Kokorin; V. A. Kokorin; N. A. Volov; A. P. Goncharov (Российский кардиологический журнал, 2010)
The paper focuses on the effectiveness and safety of bi- and monophase defibrillators in patients with paroxysmal atrial fibrillation. In bi-phase defibrillator cardioversion, sinus rhythm was restored more often, and total defibrillation energy was substantially lower than in monophase defibrillator cardioversion. No significant differences in myocardial necrosis markers were observed.